2019
DOI: 10.1080/03007995.2019.1580094
|View full text |Cite
|
Sign up to set email alerts
|

Treatment sequence network meta-analysis in Crohn’s disease: a methodological case study

Abstract: Objective: Several biologic therapies are available for the treatment of mild-to-moderate Crohn's disease (CD). This network meta-analysis (NMA) aimed to assess the comparative efficacy of ustekinumab, adalimumab, vedolizumab and infliximab in the maintenance of clinical response and remission after 1 year of treatment. Methods: A systematic literature search was performed to identify relevant randomized controlled trials (RCTs). Key outcomes of interest were clinical response (CD activity index [CDAI] reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 47 publications
1
8
0
6
Order By: Relevance
“…There is potential for further heterogeneity due to differences in the carry-over effects of the different active induction therapies. While the induction placebo rates are similar across trials, the heterogeneity of the placebo arms across maintenance trials has been demonstrated (see Supplementary Appendix 3), which was also the case in Crohn's disease 15 . Thus, the PBO arms across maintenance trials are not true common comparators, and it was therefore not considered appropriate to conduct a standard NMA of maintenance phase results only.…”
Section: Approach For the Network Meta-analysesmentioning
confidence: 87%
“…There is potential for further heterogeneity due to differences in the carry-over effects of the different active induction therapies. While the induction placebo rates are similar across trials, the heterogeneity of the placebo arms across maintenance trials has been demonstrated (see Supplementary Appendix 3), which was also the case in Crohn's disease 15 . Thus, the PBO arms across maintenance trials are not true common comparators, and it was therefore not considered appropriate to conduct a standard NMA of maintenance phase results only.…”
Section: Approach For the Network Meta-analysesmentioning
confidence: 87%
“…Инфликсимаб и адалимумаб эффективны при Пс, ПсА, БК, ЯК (уровень доказательности 1А), устекинумаб -при Пс, ПсА, БК (уровень доказательности 1А), ЯК (уровень доказательности 1В); этанерцепт, секукинумаб, иксекизумаб оказывают положительное действие при Пс, ПсА (уровень доказательности 1А), однако неэффективны и даже способствуют повышению риска обострения при ВЗК [119,120]. При назначении ГИБП пациентам с ИВЗ следует руководствоваться принципами персонифицированного подхода и управления рисками для достижения долгосрочных и безопасных результатов терапии [104,105,121,122].…”
Section: раннее назначение гибпunclassified
“…При назначении ГИБП пациентам с ИВЗ следует руководствоваться принципами персонифицированного подхода и управления рисками для достижения долгосрочных и безопасных результатов терапии [101,103,119,120].…”
Section: литература / Referencesunclassified